-(8y-3)-(-7y-8)=9

Simple and best practice solution for -(8y-3)-(-7y-8)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8y-3)-(-7y-8)=9 equation:


Simplifying
-1(8y + -3) + -1(-7y + -8) = 9

Reorder the terms:
-1(-3 + 8y) + -1(-7y + -8) = 9
(-3 * -1 + 8y * -1) + -1(-7y + -8) = 9
(3 + -8y) + -1(-7y + -8) = 9

Reorder the terms:
3 + -8y + -1(-8 + -7y) = 9
3 + -8y + (-8 * -1 + -7y * -1) = 9
3 + -8y + (8 + 7y) = 9

Reorder the terms:
3 + 8 + -8y + 7y = 9

Combine like terms: 3 + 8 = 11
11 + -8y + 7y = 9

Combine like terms: -8y + 7y = -1y
11 + -1y = 9

Solving
11 + -1y = 9

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -1y = 9 + -11

Combine like terms: 11 + -11 = 0
0 + -1y = 9 + -11
-1y = 9 + -11

Combine like terms: 9 + -11 = -2
-1y = -2

Divide each side by '-1'.
y = 2

Simplifying
y = 2

See similar equations:

| 6n=43 | | 1-2n=-10+5-n+4n | | -5+2a-8a=42 | | 3y+21=6y | | 2+3x=5(x-3) | | -3p(p+2)=-30 | | 7e^5x=924 | | -2n+2=-3n-5 | | 11x-3x+90=11x+36 | | a-5+2a-8a=42 | | 8h=168 | | x/10-4=4 | | 7a-11=38 | | 8(-4a-1)=3(10a) | | -11+5x-7+5=3+6x+x | | 5a-12=18 | | t+45=102 | | -5+2n=7n-5 | | 6q=-9+7q | | (1181*9491)/100 | | iz^2-2z^2=3 | | 1181*9491/100 | | 3/x=9/7 | | 2z/7-7=10 | | (X+15)+(x+10)=180 | | 25j^2+10j+1=0 | | 300=-0.005q^2+2.5q | | 9g=10g+6 | | .7d-15+d=2d-8-.4d | | l-3=9 | | 2(3x+4)=14-3(x-1) | | X^2-13y^2=-1 |

Equations solver categories